2017
DOI: 10.1371/journal.pone.0178616
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular motoneurons of the adult rat show higher levels of vascular endothelial growth factor and its receptor Flk-1 than other cranial motoneurons

Abstract: Recent studies show a relationship between the deficit of vascular endothelial growth factor (VEGF) and motoneuronal degeneration, such as that occurring in amyotrophic lateral sclerosis (ALS). VEGF delivery protects motoneurons from cell death and delayed neurodegeneration in animal models of ALS. Strikingly, extraocular motoneurons show lesser vulnerability to neurodegeneration in ALS compared to other cranial or spinal motoneurons. Therefore, the present study investigates possible differences in VEGF and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…There is evidence of decreased neurotrophic support and loss of NTR signaling in ALS (7,8), Although targeting NTRs offers a potential therapy for ALS (2,3,7), NTR signaling is dependent on localization to MLRs (9, 10, 25-28). Because we have previously shown that SynCav1 delivery to the CNS in vivo increases MLR-localized TrkB expression (13), we therefore performed sucrose density fraction on spinal cords to measure MLR and MLR-associated NTRs.…”
Section: Hsod1 G93a /Syncav1 + Mice Have Increased Mlr and Mlr-localimentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of decreased neurotrophic support and loss of NTR signaling in ALS (7,8), Although targeting NTRs offers a potential therapy for ALS (2,3,7), NTR signaling is dependent on localization to MLRs (9, 10, 25-28). Because we have previously shown that SynCav1 delivery to the CNS in vivo increases MLR-localized TrkB expression (13), we therefore performed sucrose density fraction on spinal cords to measure MLR and MLR-associated NTRs.…”
Section: Hsod1 G93a /Syncav1 + Mice Have Increased Mlr and Mlr-localimentioning
confidence: 99%
“…ALS is a multicomplex disease attributed to decreased neurotrophic support and loss of neurotrophin receptor (NTR) signaling (7,8), diffuse muscle weakness, muscle atrophy, spasticity, hyperreflexia (upper), and paralysis (lower) (3,4). Exogenous delivery of neurotrophins is emerging as an attractive therapeutic approach for ALS (2), yet effective neurotrophin signaling is dependent on the proper subcellular localization of NTRs to plasma membrane signaling microdomains, termed membrane/ lipid rafts (MLRs) (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In the present work, we aimed at evaluating the ability of exogenously applied VEFG to prevent the loss of the cholinergic phenotype in lesioned extraocular motoneurons of adult rats. Moreover, we have recently demonstrated that extraocular motoneurons express the VEGFR-2, also called Flk1 ( Silva-Hucha et al, 2017 ), the receptor that mainly mediates the neurotrophic effects of VEGF ( Oosthuyse et al, 2001 ; Ogunshola et al, 2002 ; Brockington et al, 2006 ; Bogaert et al, 2010 ; Tovar-y-Romo and Tapia, 2010 ; Carmeliet and Ruiz de Almodovar, 2013 ). VEGF administration was carried out peripherally through the proximal stump of the cut nerves innervating the extraocular muscles, given that this factor can travel retrogradely along axons toward the soma ( Storkebaum et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of serum miR-155 level in patients with CSVD may be one of its selfprotection mechanisms, and the strength of this self-protection mechanism may be positively correlated with the number of lesions. Further in-depth research on the level of miR-155 in the serum of CSVD will bring new ways and methods for the prevention and treatment of CSVD 20) . It is hoped that more researchers will contribute to the clearer relationship between miR-155 and inflammatory markers from different aspects, and further study of relationship between miR-155 and cerebral small vessels.…”
Section: Significance Of Changes In Serum Mir-155 Levels In Patients mentioning
confidence: 99%